2019
DOI: 10.1007/s10040-019-02033-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling managed aquifer recharge processes in a highly heterogeneous, semi-confined aquifer system

Abstract: Widespread groundwater overdraft in alluvial aquifer systems like the Central Valley (CV) in California, USA, has increased interest in managed aquifer recharge (MAR). Like most clastic sedimentary basins, recharge to the productive semi-confined CV aquifer system remains a challenge due to the presence of nearly ubiquitous, multiple confining units (silt and clay) that limit recharge pathways. Previous studies suggest the presence of interconnected networks of coarse-texture sand and gravel deposits that bypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(104 citation statements)
references
References 75 publications
11
90
3
Order By: Relevance
“…The GWO LSCN monitors groundwater levels in real-time over a critical portion of the South American River Subbasin, which may accommodate flood-based managed aquifer recharge [29,30]. Aside from occasional visits to change batteries, the installed groundwater pressure transducers and telemetry are fully automated, as is the open source data pipeline which processes sensor data and visualizes it on the web dashboard ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GWO LSCN monitors groundwater levels in real-time over a critical portion of the South American River Subbasin, which may accommodate flood-based managed aquifer recharge [29,30]. Aside from occasional visits to change batteries, the installed groundwater pressure transducers and telemetry are fully automated, as is the open source data pipeline which processes sensor data and visualizes it on the web dashboard ( Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The GWO is located in the South American River Subbasin ( Figure 2), a semi-confined, alluvial aquifer system with documented incised valley fill [29], a geological feature of great interest for its ability to accommodate relatively rapid rates of managed aquifer recharge [30,31]. The site was first instrumented on 14 November 2017 with groundwater pressure transducers and telemetry (Appendix A Figure A2).…”
Section: Methodsmentioning
confidence: 99%
“…In California, high-magnitude flood flows are likely the most accessible and largest sources of water to replenish groundwater aquifers through managed aquifer recharge [59], which might considerably slow or reverse trends in groundwater depletion. The emerging research in the strategic siting of managed aquifer recharge considers impacts on crop health [60], human health [61], the mobilization of contaminants into groundwater [62], and hydrogeologic suitability (i.e.-highly conductive flowpaths and geologic formations capable of accommodating large volumes of water, such as incised valley fills) [63]. In the San Joaquin Valley where domestic well failures peak, managed aquifer recharge alone may not be enough to offset groundwater overdraft, but coupled with a reduction in agricultural water use [46], groundwater levels may stabilize enough to prevent widespread future failure events.…”
Section: Implications For Groundwater Management and Policymentioning
confidence: 99%
“…By categorizing facies according to depositional environment rather than texture alone, the predictable geometries (i.e., facies mean lengths, proportions, and juxtapositions) of these features can be more accurately represented with sparse data. Studies that rely on these methods show strong influence of subsurface heterogeneity on groundwater/surface-water interactions and recharge processes (Lee, 2004;Fleckenstein et al, 2006;Engdahl et al, 2010;Liu, 2014), including managed aquifer recharge (MAR) (Maples et al, 2019), especially for instances when the mean lengths and proportions of high-permeability facies allow for percolation, i.e., formation of connected networks (Fogg et al, 2000;Harter, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Accurately assigning aquifer properties in models can be a challenge because they are scale dependent attributes that are challenging to measure and can vary over many orders of magnitude in typical aquifer systems (e.g., Sudicky, 1986;Gelhar et al, 1992;. While aquifer tests can accurately constrain estimates of hydraulic conductivity (K) for high-permeability facies, they are typically unreliable for estimating K of low-permeability (i.e., aquitard) facies (Fogg, 1986;Fogg et al, 1998), which have been shown to influence pumping response (Fogg et al, 2000) and be important for accommodating recharge (Maples et al, 2019). Reconciling typically sparse measurements of aquifer properties from aquifer tests with the representation of effective values in models is often the source of large uncertainty because parameterization of the properties in models is scale dependent (Sudicky and Huyakorn, 1991), and is typically achieved through model calibration.…”
Section: Introductionmentioning
confidence: 99%